Damage parameter estimation of the dual ferrite martensite steel on coercive force - Usov, V.V.; Shkatulyak, N.M.; Volchok, N.A.; Dyachok, D.A. (Functional Materials, 2018)
The elastic, strength properties, coercive force Hc and damage parameter D in different directions of the sheets of dual ferrite-martensite steel in the initial state of the factory delivery as well as after annealing at 250°C for one hour are investigated. Significant correlation relationships between mechanical and elastic characteristics with the magnitude of the coercive force were established. The corresponding regression equations with approximation coefficients of at least 0.97 are obtained. Significant correlation bonds (correlation coefficient not less than 0.95) were established between the damage parameter D, found from the magnitude of the Young modulus change during annealing, and the relative change in the coercive force Δ Hc/Hc after annealing. The obtained results open the prospects of using a non-destructive method of measuring the coercive force for estimating the damage accumulation parameter in dual ferrite-martensite steels under study on the basis of correlations between the change in the elastic modulus and the value of the coercive force.